2001
DOI: 10.1111/j.1348-0421.2001.tb02623.x
|View full text |Cite
|
Sign up to set email alerts
|

Burkholderia pseudomallei Interferes with Inducible Nitric Oxide Synthase (iNOS) Production: A Possible Mechanism of Evading Macrophage Killing

Abstract: Burkholderia pseudomallei is a causative agent of melioidosis, a life threatening disease which affects humans and animals in tropical and subtropical areas. This bacterium is known to survive and multiply inside cells such as macrophages. The mechanism of host defense against this bacterium is still unknown.In this study, we demonstrated that B. pseudomallei exhibited unique macrophage activation activity compared with Escherichia coli and Salmonella typhi, The mouse macrophage cell line (RAW 264.7) infected … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

7
114
2

Year Published

2004
2004
2019
2019

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 91 publications
(123 citation statements)
references
References 25 publications
7
114
2
Order By: Relevance
“…3). However, intracellular suppression of B. pseudomallei observed in SARM-depleted macrophages was not as efficient as IFN-␥ treatment, as previously reported by our group (28,30). It is possible that regulation of SARM by B. pseudomallei may be only partially involved in inhibition of gene expression downstream of the MyD88-independent pathway.…”
Section: Discussionsupporting
confidence: 45%
See 2 more Smart Citations
“…3). However, intracellular suppression of B. pseudomallei observed in SARM-depleted macrophages was not as efficient as IFN-␥ treatment, as previously reported by our group (28,30). It is possible that regulation of SARM by B. pseudomallei may be only partially involved in inhibition of gene expression downstream of the MyD88-independent pathway.…”
Section: Discussionsupporting
confidence: 45%
“…Although the mechanism underlying macrophage activation by TLR signaling in B. pseudomallei infection has not been fully elucidated, we previously demonstrated that this bacterium fails to activate IFN-␤ production, leading to the suppression of iNOS expression and the failure to inhibit intracellular growth of B. pseudomallei (29). However, the addition of exogenous IFN-␤ or IFN-␥ could restore the macrophage's ability to activate iNOS expression and result in enhanced killing of intracellular B. pseudomallei (28)(29)(30). In contrast, an LPS mutant lacking the O-antigenic polysaccharide moiety is more susceptible to macrophage killing, because this mutant is able to activate IFN-␤ production (2).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The results suggested that rpoS plays a critical role in resistance to hydrogen peroxide in B. pseudomallei. In addition, superoxide dismutase and catalase enzymes significantly inhibit macrophage bactericidal activity against B. pseudomallei in vitro suggesting the importance of antioxidant enzymes for the intracellular survival of this pathogen 4,5 . .…”
Section: Introductionmentioning
confidence: 99%
“…B. pseudomallei has been shown to induce less IL-8 and IkBa degradation in A549 lung epithelial cells when compared with Salmonella (28). Similarly, it induces less inducible NO synthase and TNF-a in RAW264.7 macrophages when compared with other Gram-negative bacteria (29). The muted response was postulated to be because of a less stimulatory nature of B. pseudomallei LPS (30).…”
mentioning
confidence: 99%